Translation, cultural adaptation, and psychometric evaluation of the Attention Deficit Hyperactivity Disorder Stigma Questionnaire for Portuguese speaking countries - Maria João Trigueiro; Beatriz Couto; Vítor Simões-Silva; Raquel Simões de Almeida (RevSALUS)
Introduction: Despite the growing knowledge about Attention Deficit Hyperactivity Disorder (ADHD), these people are still faced with stigma from society. Research on the stigma associated with ADHD is limited due to the lack of valid and reliable instruments. Aim: This study aimed at validating the ADHD Stigma Questionnaire (ASQ) for Portuguese speaking countries and perceiving stigma levels in a community sample. Material and Methods: The sample consisted of 762 individuals, aged between 11 and 64 years old (32.41 ±14.59 years). The validation encompassed the translation and cultural adaptation of the original version and the analysis of the psychometric properties: reliability - test-retest and internal consistency -, content validity and construct validity. Results: The internal consistency of the ASQ was very good (α = 0.93) and the test-retest values (r=0.86) support the reliability of the instrument. In construct validity, factor analysis explained 50.25% of the variance and indicated a new distribution of items 2, 3, 9 and 15 in the instrument. Women (p<0.001) and coastal residents (p=0.015) had a higher level of stigma. Conclusion: The use of the ASQ for research and clinical practice in Portuguese language countries is adequately supported by its psychometric properties. Targeted ADHD stigma and literacy campaigns could provide an important avenue for improving the broader community’s attitudes toward ADHD.